Comparative study of functional indicators in swimming and volleyball - Wissam Sahib Hassn; Haidar Majeeid Hameeid; Ali Mohammed Talib (Sport TK, 2023)
This study aimed to identify various functional indicators relevant to swimming clubs and volleyball players, and also to compare selected functional indicators between athletes engaged in swimming and volleyball. The researchers employed the descriptive method within the framework of comparative studies. The study sample comprised applicants from clubs in Baghdad, deliberately chosen to represent the pinnacle of swimming proficiency and volleyball efficiency. Each category, swimming and volleyball, consisted of 22 subjects, divided evenly into two groups, with 11 subjects in each. Functional tests utilized in this study included the heart rate test and the physical fitness test known as PWC170. There exists a notable disparity in resting heart rate between swimmers and volleyball players. While some alignment is observed in individual heart rates between the two sports, significant differences persist. Furthermore, substantial disparities in physical fitness test results, particularly the PWC170 test, are evident, with volleyball players demonstrating a six-level advantage over swimmers. Additionally, there are instances of exceptionally high PWC170 levels among swimmers, albeit in a minority of cases. There is a discernible discrepancy of eight degrees in maximum oxygen consumption (Vo2max) rates favoring volleyball players. Lastly, the Hb test results for swimmers are significantly influenced by their performance in physical fitness tests and maximum oxygen consumption, leading to a clear advantage for volleyball players in this assessment.